Endavour to gain basic function in a non-sensory stiff hand injured with electrical burn - ŞİRİN, EVRİM; CANSÜ, CENGİZ EREN (My University, 2016)
Electrical thermal injuries usually result from industrial accidents and have a mortality rate of 3-5%. They might cause functional impairment, loss of extremity and even death. Psychologic impacts can be observed also. A 34 year-old male patient admitted to our institute with an amputated upper extremity on one side and a nonfuctional hand on the contralateral side one year after an electrical injury. He had total sensorial loss on his hand. A two staged operation was planned in order to gain grip function. The frst stage was composed of release of contractures of 1st web space and MP joints of 2nd, 3rd, 4th and 5th fngers and restoration of opposition of thumb with opponensplasty. The second stage was composed of restoration of fexion of fngers with tendon grafts and restoration of pinch with adductorplasty. At the end, the patient had a partially functioning hand; at least he was able to hold a pen between his thumb and index fnger. Restoration of function and especially tendon transfer in a nonsensory extremity has only very limited indications. However psychological conditions sometimes should be taken into consideration and attempt could be made to gain a basic function
Keywords: Electrical burn; reconstruction; tendon transfer